2014
DOI: 10.1371/journal.pone.0087809
|View full text |Cite
|
Sign up to set email alerts
|

Desmosome Assembly and Disassembly Are Membrane Raft-Dependent

Abstract: Strong intercellular adhesion is critical for tissues that experience mechanical stress, such as the skin and heart. Desmosomes provide adhesive strength to tissues by anchoring desmosomal cadherins of neighboring cells to the intermediate filament cytoskeleton. Alterations in assembly and disassembly compromise desmosome function and may contribute to human diseases, such as the autoimmune skin blistering disease pemphigus vulgaris (PV). We previously demonstrated that PV auto-antibodies directed against the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
79
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(86 citation statements)
references
References 56 publications
5
79
0
Order By: Relevance
“…Recent studies have demonstrated that desmosomal components are associated with lipid rafts. (Brennan et al, 2012;Resnik et al, 2011;Stahley et al, 2014). Here, we have shown that plakophilin mutants that are unable to become palmitoylated show decreased association with lipid raft markers in sucrose-gradient centrifugation.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…Recent studies have demonstrated that desmosomal components are associated with lipid rafts. (Brennan et al, 2012;Resnik et al, 2011;Stahley et al, 2014). Here, we have shown that plakophilin mutants that are unable to become palmitoylated show decreased association with lipid raft markers in sucrose-gradient centrifugation.…”
Section: Discussionmentioning
confidence: 71%
“…7). Recent studies have demonstrated that lipid raft association is required for desmosome assembly (Brennan et al, 2012;Resnik et al, 2011;Stahley et al, 2014). Palmitoylation is likely to influence the association of desmosomal components with this highly ordered membrane microdomain and thereby affect desmosome assembly.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The latter is supported by the recent finding that the assembly of desmosomes but not of adherens junctions is lipid raft-dependent (47). Further work is not only required to elucidate these aspects but also needs to investigate whether adducin regulation is restricted to Dsg3 or affects other desmosmal adhesion molecules as well.…”
Section: Discussionmentioning
confidence: 92%
“…Some of these factors are PKC, proteolytic processing through proteins such as ADAMs and cathepsins/cystatins, EGFR signalling, raft regulation and the yet unclear mechanism of the ubiquitin-proteasome system (UPS; Nekrasova & Green, 2013;Yin et al, 2005;Stahley et al, 2014;Loffek et al, 2012).…”
Section: Modulation Of Desmosomal Architecture and Adhesionmentioning
confidence: 99%